2012
DOI: 10.1186/1743-7075-9-49
|View full text |Cite
|
Sign up to set email alerts
|

Combined dietary folate, vitamin B-12, and vitamin B-6 intake influences plasma docosahexaenoic acid concentration in rats

Abstract: BackgroundFolate, vitamin B-12, and vitamin B-6 are essential nutritional components in one-carbon metabolism and are required for methylation capacity. The availability of these vitamins may therefore modify methylation of phosphatidylethanolamine (PE) to phosphatidylcholine (PC) by PE-N-methyltransferase (PEMT) in the liver. It has been suggested that PC synthesis by PEMT plays an important role in the transport of polyunsaturated fatty acids (PUFAs) like docosahexaenoic acid (DHA) from the liver to plasma a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…Furthermore, data have shown uridine can stimulate phospholipid synthesis without diminishing acetylcholine synthesis or release in rat brain slices; and dietary supplementation with UMP increases acetylcholine level and release in striatum of aged rat [54,55]. Supplemental intakes of B vitamins (folate and vitamins B 12 and B 6 ) and dietary phospholipids may serve as cofactors to increase the availability of choline and DHA for neuronal membrane phospholipid synthesis [45,46,56]. Uridine or DHA, which promote phospholipids' synthesis, also have been shown to increase synaptic protein levels, enhance neurite outgrowth, and increase dendrite spine density, all indicative of synapse formation [52,[57][58][59][60].…”
Section: Nutrient Requirements For Synapse Formationmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, data have shown uridine can stimulate phospholipid synthesis without diminishing acetylcholine synthesis or release in rat brain slices; and dietary supplementation with UMP increases acetylcholine level and release in striatum of aged rat [54,55]. Supplemental intakes of B vitamins (folate and vitamins B 12 and B 6 ) and dietary phospholipids may serve as cofactors to increase the availability of choline and DHA for neuronal membrane phospholipid synthesis [45,46,56]. Uridine or DHA, which promote phospholipids' synthesis, also have been shown to increase synaptic protein levels, enhance neurite outgrowth, and increase dendrite spine density, all indicative of synapse formation [52,[57][58][59][60].…”
Section: Nutrient Requirements For Synapse Formationmentioning
confidence: 97%
“…In a recent systematic review, the pooled data from nine casecontrol studies showed that patients with AD have low serum levels of folate and vitamin B 12 , which are associated with increased homocysteine (Hcy) levels [43]. Increased Hcy and low B vitamin status are associated with reduced mobilization of DHA from liver to plasma and peripheral tissue [44,45], and with reduced choline synthesis and increased choline utilization [46][47][48].…”
Section: Lower Micronutrients and Fatty Acid Status In Admentioning
confidence: 98%
“…Hypomethylation of IGF2 P3 is responsible for upregulated IGF2 transcription and has an active role in osteosarcoma and hepatoblastoma (12,27). Several clinical studies have shown a positive correlation between plasma DHA concentration and erythrocyte folate level or serum vitamin B 6 and B 12 , reported to be methylation modulators of imprinted genes (25,47,49). Interestingly, a choline-and methionine-deficient diet revealed a decrease of repressive dimethylation at histone H3 lysine 9 (H3K9) within H19 promoter as well as Igf2 P2 and P3 (6).…”
Section: Discussionmentioning
confidence: 99%
“…4 Certain B vitamins -specifically folate (vitamin B 9 ), B 6 and B 12 reduce blood homocysteine levels. 5 However, studies assessing the relationship between B vitamins and cognitive performance have produced mixed results. One study reported that taking high-dose B vitamin supplements (5mg folate, 25mg vitamin B 6 and 1mg vitamin B 12 daily) for 18 months did not slow the decline in scores on the cognitive subscale of the Alzheimer's Disease Assessment Scale (ADAScog) among patients with mild-to-moderate Alzheimer's disease.…”
Section: Homocysteine and B Vitaminsmentioning
confidence: 99%